Public health nursing education in Turkey: a national survey - KADIOĞLU, HASİBE (WILEY, 2013)
Aim: To investigate public health nursing content in undergraduate and postgraduate programmes in Turkey. Methods: This study included all of the nursing schools in Turkey that provide university level education. The data were collected through a self-administered questionnaire designed to identify the existing status of undergraduate and postgraduate public health nursing education between February 2011 and June 2011. The questionnaire was completed only by the head of the department of public health nursing in each school. Data were analysed with descriptive statistics using SPSS for Windows 17.0 software. Results: The study achieved a response rate of 72.5%. All participants reported offering a course in public health nursing in their undergraduate programmes. Fourteen (24.1%) participants reported offering Master of Science degrees in public health nursing. Seven (12.1%) participants reported offering doctorate degrees in public health nursing. In the responding schools, the public health nursing course was given in one semester (14 weeks) for an average of 5.54 +/- 1.43 h/week for theory and an average of 13.48 +/- 5.11 h/week for clinical practice. Of the participants, 43 (74%) reported problems related to public health nursing education. Conclusion: There are problems in Turkey with regard to public health nursing education. The nursing school curriculum must be revised on a national level if public health nursing is to be revived and strengthened.
Keywords: Postgraduate Education; Public Health Nursing; Undergraduate Education; GRADUATE-EDUCATION